Fly ash for the removal of Mn(II) from aqueous solutions and wastewaters - Sharma Y.C.; Uma; Singh S.N.; Paras; Gode F. (My University, 2025)
Application of fly ash, a waste material of thermal power plants has been investigated for the removal of manganese from aqueous solutions and wastewaters. The removal was found to be highly concentration dependent and higher removal (%) was obtained at low concentrations of Mn(II) in the solutions. The removal decreased from 74.2 to 47.2% by increasing the Mn(II) concentration from 1.5 to 5.0 mg l-1 at 298 K, pH 8.0, and 1.0 × 10-2 M NaClO4 ionic strength. Removal, however, decreased from 51.3 to 7.2% by increasing the adsorbent particle size from 100 to 250 μm. The process of Mn(II) is exothermic in nature. Thermodynamic parameters namely free energy, ΔG°, enthalpy, ΔH°, and entropy, ΔS° were calculated and were found to be -0.72, 7.34 and 28.28 kcal mol-1 at 298 K. Heat of adsorption as a function of surface coverage was also calculated and was 8.20 kcal mol-1 at 298 K. The data can be used for designing treatment plants for the treatment of Mn(II) rich waters and wastewaters. © 2007 Elsevier B.V. All rights reserved.